2008
DOI: 10.1063/1.2833821
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoimpedance, magnetoresistance, and magnetic properties of nanometric CMR manganites

Abstract: The effects of nanometric grain size (ϕ=14–28nm) modulation on the behavior of magnetoimpedance (MI), magnetoresistance, and magnetic properties of chemically synthesized a series of single-phase soft ferromagnetic nanocrystalline colossal magnetoresistance La0.7Sr0.3MnO3 (LSMO) manganites at room temperature have been reported. From the frequency and magnetic filed dependent MI measurement it is found that the MI percent increases with the increase in nanometric grain size (ϕ) for this series of samples. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 15 publications
2
6
0
Order By: Relevance
“…By increasing the particle size, the spontaneous magnetization and curvature are increased which indicates that the magnetic order in the samples are increased. This behavior has been also reported for LSMO nanoparticles [26,27].…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…By increasing the particle size, the spontaneous magnetization and curvature are increased which indicates that the magnetic order in the samples are increased. This behavior has been also reported for LSMO nanoparticles [26,27].…”
Section: Resultssupporting
confidence: 62%
“…From Fig. 4, Arrott plot shows a strong convex curvature with a finite spontaneous magnetization which is a signature of ferromagnetic phase of the samples [26,27]. Spontaneous magnetization can be estimated by linear fitting of the high magnetic field part of the M 2 -H/M curve and intercepts it with the M 2 axis.…”
Section: Resultsmentioning
confidence: 98%
“…8. ABK plot shows a strong convex curvature with a finite spontaneous magnetization which is a signature of ferromagnetic phase of S2 sample [27,28]. Due to the existence of size distribution, the magnetic nanoparticles of the S2 sample have different blocking temperatures.…”
Section: Resultsmentioning
confidence: 96%
“…In contrast, the evolution of Curie temperature claimed for these new materials was highly controversial. Some authors reported a decrease of T C with decreasing crystallite size either on La 1Àx Ca x MnO 3 16,20 or La 1Àx Sr x MnO 3 8,17,19,23,24,26,28 samples with x close to 0.3. This evolution was often interpreted in terms of MDL which contributed to destabilize the magnetic order.…”
Section: Introductionmentioning
confidence: 99%